Multi-family Buildings - Architectural Trends of the Last Three Decades in Poland. Issue 8 (February 2019) - Tokajuk, Andrzej
Abstract: During last almost three decades' architecture in Poland is developing in a very dynamic way, some Polish new projects became famous and have won international competitions (e.g. sport arenas in Warsaw, Gdansk, Art Garden in Cracow, Philharmonic Hall in Szczecin, Cultural Centre in Szczecin, Opera House in Bialystok, etc.). But in the transformation period in Poland we can find also many significant examples of housing architecture as well one family houses as multi-family (residential) buildings. In the article the author is taking the trial of synthetic analysis of the evolution of multi-family buildings architectural forms in Poland after 1989. Based on the analysis of a few hundred housing projects, the author identifies the main - in his opinion - trends of creating the forms mentioned above, ideas of design these buildings and elements of their architecture – the architectural game. The author used the following methods during the research - case studies analysis, made in the chronological way, which was predicted by collecting materials, identification of new concepts using the analysis of architectural composition of elevations and details. As the result of research they have been identified following trends and styles as the most important: creative pluralism, traditionalism, postmodernism, new modernism, architectural game of elevation details, concepts - "idea of the form". These trends create a kind of evolution line corresponding chronological development. The research proved that the quality concepts of architecture of multi-family buildings in Poland in the mentioned period of time increased very much and now they represent high quality European level. Some of Polish housing projects realized during last 28 years became famous and have been marked in the history of Polish and European architecture. Presented in the article creative attitudes and projects are not the closed list, they will be developed and completed during next research.